REMOTE SPECIAL COURSE «LATIN. BOTANY TERMINOLOGY» AS A MEANS OF BECOMING A PROFESSIONAL AND TERMINOLOGICAL COMPETENCE OF BIOLOGY TEACHER - Pererva Victoria (Borys Grinchenko Kyiv Metropolitan University, 2019)
The essence and advantages of distance learning as a form of organization of independent work in the professional training of future specialists are revealed. Formation of a professional term system is considered as a prerequisite for the formation of professional-terminological competence of a future teacher. Independent work Outside the classroom process is expanding the amount of material to be absorbed (both theoretical and applied), assisting in preparing for the tests and examinations in professional disciplines. Today, integration of modern pedagogical and information technologies, their wide introduction into the educational process is very important. In the system of vocational education, issues of the culture of professional communication, are of particular importance. Imperfect knowledge of the professional terminology leads to the appearance of a significant number of typical errors, reducing the level of the culture of speech. An important role in mastering students' knowledge of the special course «Latina. Botany terminology» is given to independent work, which gradually becomes one of the leading forms. Application of new information and telecommunication technologies in the educational process, creation, and use of modern electronic teaching aids and distance courses solve complex tasks of forming a single educational information environment. Distance learning course «Latina. Botany Terminology» for future biology teacher is allows each student to work in an individual mode under the guidance of teachers. The content and structure of the distance e-learning course «Latin. Botany Terminology» for students of the Natural Department of Pedagogical Institutions of Higher Education is shown. The purpose of the distance special course, is to enrich the personality language culture, understanding the semantics and etymologies of biological terms